Dynamics of reflection of corporal potential of teenagers under act of employments on the offered technology of fitness. - Kibal'nik Oksana Yakovlevna (Kharkov National Pedagogical University, 2011)
The main point of presented fitness-technologies conception is in natural combination of modern trends and means of health-improving fitness and theoretical knowledge of its use. The aim of the work is efficiency assessment of developed technologies. The effect of these technologies on the level of teenagers self-realisation of their own physical experience and peculiarities of their life prospects design was studied. It was proved that under the effect of experiment factor the quantity of teenagers, who more positively conceive No. 1, show confidence in goals achievement, are ready to overcome misfortune due to their possibilities and self-activity, is increased.